2024
DOI: 10.1002/cre2.843
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ceramic materials and tooth preparation design on computer‐aided design and computer‐aided manufacturing endocrown adaptation and retentive strength: An in vitro study

Ahmed Farghal,
Karim Dewedar,
Mohammed H. AbdElaziz
et al.

Abstract: ObjectivesTo evaluate how various tooth preparation designs impact the adaptation—both at the margins and internally—and the retentive strength of computer‐aided design and computer‐aided manufacturing (CAD/CAM) produced endocrowns.Materials and Methods60 extracted human mandibular first molars were endodontically treated and assigned into three groups (n = 20) according to the tooth preparation design: Group N: butt joint design, Group F and F1 received 1‐ and 2‐mm circumferential ferrule preparation, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The endocrowns’ accuracy and adaptation might depend on the tooth type and form; a laboratory study reported that mandibular endocrowns showed better adaptation than maxillary endocrowns [ 32 ]. In terms of endocrown preparation designs, there are several laboratory studies executed to evaluate the effect of endocrown pulpal extensions on fracture resistance [ 33 , 34 ]; others extend the preparation on the axial surface utilizing ferrule preparation [ 17 , 18 , 35 ]. The presence of the ferrule design can improve fracture resistance by acting as a reciprocal support against laterally exerted stresses [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The endocrowns’ accuracy and adaptation might depend on the tooth type and form; a laboratory study reported that mandibular endocrowns showed better adaptation than maxillary endocrowns [ 32 ]. In terms of endocrown preparation designs, there are several laboratory studies executed to evaluate the effect of endocrown pulpal extensions on fracture resistance [ 33 , 34 ]; others extend the preparation on the axial surface utilizing ferrule preparation [ 17 , 18 , 35 ]. The presence of the ferrule design can improve fracture resistance by acting as a reciprocal support against laterally exerted stresses [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%